Kenaf and kenaf-rubberwood hybrid particleboards - Abdul Halip, Juliana; Lee, Seng Hua; Md. Tahir, Paridah; Osman Al-Edrus, Syeed SaifulAzry; Md Ishak, Siti Mastura; Selimin, Mohamad Ali; Ab Hamid, Abdullah Al Rashid (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Kenaf (Hibiscus cannabinus) stem which consists of whole stem (KWS), core (KC) and bast (KB) were used to fabricate homogeneous and hybrid kenaf-rubberwood particleboards. Two types of panels namely homogeneous (100%RW, 100%KWS, 100%KC and 100%KB) and hybrid (70%RW- 30%KWS, 70%RW- 30%KC and 70%RW- 30%KB) particleboards were manufactured and examined through compaction and void evaluations. Findings show that hybrid panels consisting of 70% RW and 30% KWS and homogeneous 100%KWS give better compaction and less voids as compared to other homogenous and hybrid panels. The panel made from 100% KWS was observed to have more flattened and compressed cells compared to other homogeneous panels. A presence of RW particle apparently reduces the void content and provides better compaction in the hybrid panels.